2017
DOI: 10.9790/264x-03021012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Skills of Phlebotomy Technique among Nursing Staffs of a Teaching Hospital

Abstract: Introduction: Phlebotomy is a commonly done invasive technique, performed either for diagnostic or therapeutic purpose. A thorough knowledge and skills are to be ensured in the health care professionals who carry out this procedure regularly so as to ensure patient safety and minimize pre analytical errors in laboratory investigations. Aim of the present study was to assess the theoretical knowledge and practical skills of nursing staffs to carry out the phlebotomy procedure. Methodology: A validated questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…They also felt that it is very essential to bring an awareness regarding causes of hemolysis during sample collection and factors contributing to pre analytical errors necessitates an intervention, in the form of training program. 17 Cai et al conducted a study in China from four economic region, where 13 specialized hospital were included in the study and they found that only a small proportion of the nurses (15.5%) were aware of the correct order of multi-tube blood sampling. There was requirement to strengthen education with a focus on phlebotomy.…”
Section: Resultsmentioning
confidence: 99%
“…They also felt that it is very essential to bring an awareness regarding causes of hemolysis during sample collection and factors contributing to pre analytical errors necessitates an intervention, in the form of training program. 17 Cai et al conducted a study in China from four economic region, where 13 specialized hospital were included in the study and they found that only a small proportion of the nurses (15.5%) were aware of the correct order of multi-tube blood sampling. There was requirement to strengthen education with a focus on phlebotomy.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Cai et al conducted in China, the level of knowledge on phlebotomy among nurses was not found to be quite satisfactory [ 9 ]. In another study conducted by Adiga et al in 2017, the majority of the questions assessing the knowledge domain were correctly answered and no significant difference was found in the knowledge level, between the groups based either on age or number of years of experience [ 2 ]. Correct patient identification is crucial to ensure patient safety and proper patient identification must rely on at least two independent identifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory services have become an integral part of the modern healthcare sector, and venous blood collection is one of the most common invasive procedures. Even though it is thought to be a safe procedure, it is associated with its risks such as needle stick injuries and preanalytical errors [ 1 , 2 ]. To perform successful phlebotomy, both theoretical knowledge, as well as practical skills, are required [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of hemoglobin in plasma can result in multiple-organ failures and potentially death. For all of these conditions, then, a cost-effective, compact, point-of-care analyzer for detecting Hgb in blood plasma would be of great benefit (Archibong et al, 2015;Adiga and Yogish, 2016;Šimundić et al, 2010).…”
Section: Introductionmentioning
confidence: 99%